“I’ll do it on my own, but I’m never alone”[1 p. 402]: lived experience and practitioner perspectives of autonomy in longstanding and severe eating disorder treatment and recovery–a rapid evidence review - Freddy Burke; Maree Higgins; Maureen MacGinley (Journal of Eating Disorders)
Abstract Purpose To examine autonomy within treatment and recovery from longstanding and severe eating disorders (EDs). Background The typically early age of onset, high incidence, and prolonged duration of EDs, has a high personal, relational, and financial burden for people who experience them. Current treatment practices rely on the exertion of external control and influence which has profound impacts on people living with EDs as well as the relationship and interactions between them and their treating professionals. Yet scant research focuses specifically on how people with EDs, especially longstanding and severe presentations, experience autonomy. Centring the lived experience voice is essential to deconstruct power imbalances and develop more effective recovery pathways. Methods A Rapid Evidence Review answered the research question, How do people with longstanding and severe eating disorders experience autonomy and recovery? Five electronic databases, the International Journal of Eating Disorders, and topic-specific grey literature from 2000–2021 were systematically searched. Twenty articles met the inclusion criteria. All findings and primary lived experience quotations relevant to the review topic were extracted, charted, and analysed. Reflexive Thematic Analysis (Braun and Clarke in Qual Psychol 9:3–26, 2021; Braun and Clarke in Qual Res Psychol 3:77–101, 2006;) was undertaken to inform the key findings and discussion. Findings The researchers identified four central themes that characterise the experience of autonomy in treatment and recovery for people with longstanding and severe EDs: Self versus ED, Self in Treatment, Self in Recovery, and Others in Relation to Self. Novel theoretical contributions to understanding longstanding and severe EDs include the ‘Lack of Autonomy’ Loop, ‘Relational Autonomy’ and the diversity of definitions of recovery. Discussion This review highlights the critical role of autonomy in the treatment and recovery of individuals with longstanding and severe EDs. It underscores the importance of addressing past trauma and integrating trauma-focused therapy within ED treatment. The findings advocate for collaborative, tailored, and autonomy-supportive approaches that empower individuals to break the cycle of disempowerment and promote sustained recovery. Conclusion The review highlights the need for conceptual and practice development to leverage desire-focused, relational approaches for effective healing and recovery.